Restaurant Tax Revenue in Enhancing Local Revenue in the City of Ambon - Sakir, Ahmad Rosandi (Indonesian Scientific Publication, 2023)
Ambon City Regulation Law No. 2 of 2011, in CHAPTER 1 Article 1 paragraph 12, clarifies that restaurant tax pertains to the services provided by restaurants. Additionally, in Article 1 paragraph 13, it defines a restaurant as an establishment offering food and/or beverages, encompassing cafeterias, stalls, bars, and similar entities, including food/catering services. Sections 12 and 13 specify that the restaurant tax is calculated based on the payment received or due to the restaurant (Article 12), and the tax rate is set at 10% (Article 13). The restaurant tax significantly contributes to the growth of local own-source revenue in Ambon City, as evidenced by research data showing a consistent annual increase. However, there remains a need for governmental (tax officer) evaluation to enhance public awareness (taxpayers), particularly concerning restaurant taxes, ensuring sustained and escalating local own-source revenue through this tax